2002
DOI: 10.1007/s00420-002-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Markers of insulin resistance in day and shift workers aged 30-59 years

Abstract: Shift work may be associated with IR syndrome in workers younger than 50 years. These relations may be underestimated mainly by broad definition of shift work and healthy-worker effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 33 publications
8
82
1
4
Order By: Relevance
“…Such results were similar to that of Di Lorenzo et al (2003) who examined the influence of shift work on metabolic and cardiovascular risk factors among subjects working in a chemical industry in southern Italy and found that shift workers had higher glucose levels (Di Lorenzo et al, 2003). In another crosssectional study of Japanese male blue collar workers, Nagaya et al (2002) reported that shift workers were more likely than day-time workers to have high fasting serum glucose (Nagaya et al, 2002). Additionally, a study by Ye et al (2013) reported similar associations between shift work and the metabolic syndrome in female workers from the Daegu area Dyeing Industrial Complex, Korea, and found that the shift work group had significantly higher FBS levels.…”
Section: Discussionsupporting
confidence: 83%
“…Such results were similar to that of Di Lorenzo et al (2003) who examined the influence of shift work on metabolic and cardiovascular risk factors among subjects working in a chemical industry in southern Italy and found that shift workers had higher glucose levels (Di Lorenzo et al, 2003). In another crosssectional study of Japanese male blue collar workers, Nagaya et al (2002) reported that shift workers were more likely than day-time workers to have high fasting serum glucose (Nagaya et al, 2002). Additionally, a study by Ye et al (2013) reported similar associations between shift work and the metabolic syndrome in female workers from the Daegu area Dyeing Industrial Complex, Korea, and found that the shift work group had significantly higher FBS levels.…”
Section: Discussionsupporting
confidence: 83%
“…Disruption of these processes is exemplified by the extreme circumstances of reversal of day/night working patterns seen in some shift workers. Lund et al [40] reported that maladaption of endogenous circadian rhythms in shift workers was associated with increased insulin resistance and elevated postprandial triglyceride levels, findings consistent with other studies in this field [44][45][46][47]. In addition, shift work is associated with an increased risk of cardiovascular disease [46,47], reported in one study as conveying a 1.6-and 3.0-fold increased risk for men and women, respectively, in the 45-55 year age group [46,48].…”
Section: Man Diabetes and Cardiovascular Diseasementioning
confidence: 57%
“…Recently, common criteria for the clinical diagnosis of metabolic syndrome have been proposed by several major organizations in the Joint Scientific Statement in an attempt to unify all presented criteria [17]. Higher prevalence of the metabolic syndrome has been demonstrated among shift workers [18][19][20][21]. A recent study by De Bacquer et al demonstrates that the risk of development of the metabolic syndrome gradually increases independently of the accumulated years of shift work.…”
Section: Metabolic Syndromementioning
confidence: 99%